1, 4-Butanediol overdose mimicking toxic alcohol exposure. (3rd March 2020) - Stefani, Maurizio; Roberts, Darren M.
Abstract: Context: 1, 4-butanediol (1, 4-BD) is a gamma-hydroxybutyrate (GHB) analogue with a similarly narrow therapeutic window that is becoming a more common cause of recreational overdose. Reports of confirmed exposures are limited. Case details: A 44 year-old man who had consumed alcohol subsequently became unconscious after ingesting what was thought to be GHB. The presentation was not entirely consistent with GHB poisoning, including a longer duration of unconsciousness and features that mimicked toxic alcohol exposure including a high anion gap metabolic acidosis (HAGMA) and osmol gap. The patient was treated supportively with intubation, haemodiafiltration and intravenous ethanol until the diagnosis was refined using specific laboratory testing. The concentration of 1, 4-BD was the highest reported in the literature and the outcome favourable. Discussion: This case highlights pharmacokinetic issues peculiar to 1, 4-BD, including the interaction with ethanol which delays the onset of psychoactive effects from 1, 4-BD's metabolite GHB, and dose-dependent pharmacokinetics. In overdose, 1, 4-BD can induce a HAGMA and other features of toxic alcohol poisoning. Managing an unconscious patient with these features can prompt certain treatments until the diagnosis is refined, which can require specific laboratory testing to identify the culprit. The actual risk of toxic alcohol and other causes is adjusted on a case-by-case basis from the history of exposure and local epidemiology of substance use and poisoning.